(3x+23)+95(7x-4)(9x-6)=540

Simple and best practice solution for (3x+23)+95(7x-4)(9x-6)=540 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+23)+95(7x-4)(9x-6)=540 equation:



(3x+23)+95(7x-4)(9x-6)=540
We move all terms to the left:
(3x+23)+95(7x-4)(9x-6)-(540)=0
We get rid of parentheses
3x+95(7x-4)(9x-6)+23-540=0
We multiply parentheses ..
95(+63x^2-42x-36x+24)+3x+23-540=0
We add all the numbers together, and all the variables
95(+63x^2-42x-36x+24)+3x-517=0
We multiply parentheses
5985x^2-3990x-3420x+3x+2280-517=0
We add all the numbers together, and all the variables
5985x^2-7407x+1763=0
a = 5985; b = -7407; c = +1763;
Δ = b2-4ac
Δ = -74072-4·5985·1763
Δ = 12657429
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{12657429}=\sqrt{9*1406381}=\sqrt{9}*\sqrt{1406381}=3\sqrt{1406381}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7407)-3\sqrt{1406381}}{2*5985}=\frac{7407-3\sqrt{1406381}}{11970} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7407)+3\sqrt{1406381}}{2*5985}=\frac{7407+3\sqrt{1406381}}{11970} $

See similar equations:

| x-9/4=-10 | | 4c=7.8 | | 5y+y–2=0 | | 18+v=43 | | 3x–7–2/39x–6)=15 | | 160÷x=8 | | 6.56-4.1n=5.2-4.3n | | (4-3i)(7+2i)=0 | | x/100=25/1000 | | -3.4x+12=1.5x-23 | | (2x+29)=(10x-27 | | 2x+48=70 | | 3p-(6+8)=4 | | 9/27=10x | | 2x+48=7- | | 4^-2x+3=4^-x | | 5f=f+24 | | x/100=50/1000 | | q–9.45=11 | | 3.5+40x=71.5 | | 40+3.5x=71.5 | | q–9.45=11) | | 5^3-2n=125 | | 9)q–9.45=11 | | 75=3.5+40x | | y-2.7=7.2 | | 75=40+3.5x | | u+7.64=9.78 | | —9=4x+7 | | 2x-1+25+110=180 | | x+6.8=9.59 | | 9.25+18.75p=178 |

Equations solver categories